2017
DOI: 10.18632/oncotarget.18014
|View full text |Cite
|
Sign up to set email alerts
|

The MMP2 rs243865 polymorphism increases the risk of prostate cancer: A meta-analysis

Abstract: Prostate cancer is a common cancer in men. However, the association between the rs243865 single-nucleotide polymorphisms in the matrix metalloproteinase 2 gene (MMP2) and the risk for prostate cancer is inconclusive. We searched the PubMed, EMBASE, Cochrane Library, and the Chinese CNKI and WANFANG databases for the relevant literature. Data were extracted and pooled results were estimated from odds ratios (OR) with 95% confidence intervals (95% CIs). The quality of included studies was assessed, and publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(23 reference statements)
1
4
0
Order By: Relevance
“… 7 Conversely, both the previous meta-analyses included this study and thus concluded significant association. 17 , 18 For MMP1 rs1799750, our paper enrolled two additional studies 32 , 33 compared with one previous meta-analysis, 17 and obtained a similar result. The major strengths of our paper lie in focusing on the relationship between MMP polymorphisms and prostate cancer risk comprehensively and systematically.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“… 7 Conversely, both the previous meta-analyses included this study and thus concluded significant association. 17 , 18 For MMP1 rs1799750, our paper enrolled two additional studies 32 , 33 compared with one previous meta-analysis, 17 and obtained a similar result. The major strengths of our paper lie in focusing on the relationship between MMP polymorphisms and prostate cancer risk comprehensively and systematically.…”
Section: Discussionsupporting
confidence: 61%
“…We noticed two previous meta-analyses had investigated the relationships of MMP1 rs1799750 or MMP2 rs243865 and prostate cancer risk. 17 , 18 We read these carefully with great interest. Neither included other MMP polymorphisms, except for MMP1 rs1799750 and MMP2 rs243865.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prostate cancer, its overexpression by malignant prostatic epithelium is considered to contribute to increased tumor invasiveness, migration, metastasis, higher tumor stage, higher Gleason score and is related to shorter disease-free survival, but it is also involved in prostate cancer development (4,5,15). It is also believed that MMP2 rs243865 polymorphisms are related to higher risk of prostate adenocarcinoma and metastasis (17). MMP2 and TGFβ are closely related since MMP2 stimulates EMT through the activation of TGFβ by solubilizing TGF-β of extracellular matrix (13).…”
Section: Discussionmentioning
confidence: 99%
“…Noncoding SNP mutations are often associated with tumor development. [21][22][23][24][25] Currently, studies of SNPs have mainly focused on coding SNPs. The role of noncoding SNPs in disease development remains obscure.…”
Section: Introductionmentioning
confidence: 99%